Analisis Perbandingan Tingkat Stabilitas Keuangan Perbankan Syariah dan Konvensional di Indonesia - Alvien Nur Amalia (FEB Universitas Sultan Ageng Tirtayasa, 2018)
This study aims to compare the level of financial stability of Islamic banking with conventional banking in Indonesia by using samples of 6 Islamic banks and 38 conventional banks which are categorized as commercial banks of business groups (BUKU) 1 and 2. Secondary data is used in the observation period beginning in 2011 -2015 using t-test. The results explain that there are differences in the level of financial stability of Islamic banking than conventional when viewed from the average value of Z-Index. The average value of Z-Index of Islamic banking is greater than conventional banking, so it can be said that the level of financial stability of Islamic banking is better than conventional banking. However, when viewed from the average value of NPF / L, there is no difference in the level of financial stability between Islamic and conventional banking.